Mechanical Vibration Test Equipment Design Laboratory Capacity for Automotive Industry - Firmansyah, Ricky; Sugeng, Margono (NBRI Press, 2023)
Vibration monitoring can also be used to find vibration levels caused by misaligned shafts and unbalanced masses, shaft misalignment of which is the root of vibration. In the UNDIRA Mechanical Engineering laboratory there is no mechanical vibration test equipment. In making the table frame and shaft, of course, it must be calculated accurately. Here the Solidworks 2017 application is used to make it easier to analyze the strength of the table frame and shaft. In simulating the strength of the Solidworks 2017 table frame and shaft, the types of materials used are Galvanized Steel and AISI 1018 and loading is carried out on the frame with a load of 7.85 N on the table frame and 2.61 N on the shaft. The simulated results obtained a stress of 7,539 x 104 (N/m²) with a displacement of 9.597 mm. The simulation results obtained safety factor values of 4.4 and 2.7. Based on Davis in the book “The Testing of Engineering Materials”, the strength of the table frame of mechanical vibration test equipment is able to support the performance of the machine during use.